2013
DOI: 10.1073/pnas.1301672110
|View full text |Cite
|
Sign up to set email alerts
|

Nucleostemin deletion reveals an essential mechanism that maintains the genomic stability of stem and progenitor cells

Abstract: Stem and progenitor cells maintain a robust DNA replication program during the tissue expansion phase of embryogenesis. The unique mechanism that protects them from the increased risk of replication-induced DNA damage, and hence permits self-renewal, remains unclear. To determine whether the genome integrity of stem/progenitor cells is safeguarded by mechanisms involving molecules beyond the core DNA repair machinery, we created a nucleostemin (a stem and cancer cell-enriched protein) conditional-null allele a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 19 publications
(24 reference statements)
2
77
0
Order By: Relevance
“…Regardless, until such evidence is presented, it is scientifically inaccurate to refer to mammalian nucleostemin as a nucleolar GTPase or assume it functions as a GTPase enzyme. The biological importance of nucleostemin has never been in doubt, as it is well established that nucleostemin makes key contributions to blastocyst formation (Beekman et al, 2006;Zhu et al, 2006), embryogenesis (Meng et al, 2013), postnatal tissue regeneration Shugo et al, 2012), cancer development (Lin et al, 2010;Sijin et al, 2004;Tamase et al, 2009) and reprograming to pluripotency (Qu and Bishop, 2012).…”
Section: History and Mysteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, until such evidence is presented, it is scientifically inaccurate to refer to mammalian nucleostemin as a nucleolar GTPase or assume it functions as a GTPase enzyme. The biological importance of nucleostemin has never been in doubt, as it is well established that nucleostemin makes key contributions to blastocyst formation (Beekman et al, 2006;Zhu et al, 2006), embryogenesis (Meng et al, 2013), postnatal tissue regeneration Shugo et al, 2012), cancer development (Lin et al, 2010;Sijin et al, 2004;Tamase et al, 2009) and reprograming to pluripotency (Qu and Bishop, 2012).…”
Section: History and Mysteriesmentioning
confidence: 99%
“…One study has shown that nucleostemin is able to reduce telomere damage through modification of telomeric repeat Science (2014Science ( ) 127, 3885-3891 doi:10.1242 binding factor 1 (TRF1, also known as TERF1) and recruitment of promyelocytic leukemia protein isoform IV (PML-IV) in telomerase-negative human cancer cells (Hsu et al, 2012). Two reports have identified that it protects the genome integrity of stem or progenitor cells by promoting the recruitment of RAD51, the core component of the homologous recombination machinery, to stalled replication-induced DNA damage foci Meng et al, 2013) (Fig. 1).…”
Section: History and Mysteriesmentioning
confidence: 99%
“…uS3) has been reported to act as an apurinic/apyrimidinic endonuclease in both nuclear and mitochondrial base excision repair (Kim et al 2013), while nucleostemin/GNL3 has been implicated in the recruitment of RAD51 to stalled replication forks Meng et al 2013), and Nol12 has D r a f t 5 been identified as an important protective factor against oxidative DNA damage (Scott et al 2016). Most strikingly, two proteins -nucleophosmin (NPM1) and nucleolin (NCL) -are required for optimal activity of multiple independent DNA repair pathways, and their dysregulation has been reported in numerous cancers, in particular leukemias and other myeloproliferative disorders (Berger et al 2015;Colombo et al 2011;Federici et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we believe that the conclusion reached by Romanova et al might be confounded by unsuspected issues surrounding the immediate versus longterm effects of nucleostemin depletion, as well as the interconnecting relationship between nucleolar function and cell cycle. Furthermore, while the present investigation was under way, a parallel study suggested that there is a direct molecular recruitment of nucleostemin to DNA damage sites, where it interacts with the DNA repair protein RAD51 (Meng et al, 2013). This also alerted us to the possibility that nucleostemin is involved in genome protection and not rRNA synthesis.…”
Section: Discussion the Hypothesismentioning
confidence: 99%
“…In this respect, it is noteworthy that effects on ribosome synthesis have been observed following two rounds of RNAi-mediated nucleostemin knockdown over a period of 5 days (Romanova et al, 2009a;Romanova et al, 2009b). Motivated by the recent discovery of a role for nucleostemin in protecting telomeres and the genome integrity of stem and progenitor cells (Hsu et al, 2012;Lin et al, 2013;Meng et al, 2013;Yamashita et al, 2013), we began to consider whether the accumulation of DNA damage, rather than impaired ribosome production, is actually the initial event following nucleostemin depletion. Using human breast cancer MDA-MB-231 cells, we found that DNA damage arises as early as 12 hours after the initiation of nucleostemin depletion, without incurring a significant effect on rRNA synthesis or nucleolar structure for up to 48 hours.…”
Section: Introductionmentioning
confidence: 99%